THE EFFECT OF COMPANY SIZE, TAX AND DEBT COVENANT ON ACCOUNTING CONSERVATISM IN COMPANIES FOOD AND BEVERAGES - Dwi Wahyuni; Feronika Rosalin; Echi Kurniati; Dian Utari; Ahmad Fikriyansyah (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
This study aims to determine whether company size, tax, and debt covenants have a partial and simultaneous effect on accounting conservatism in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2017-2020. The data analysis method in this research is the descriptive method and verification method. The sampling method used was the purposive sampling method.The results of the study simultaneously prove that there is at least one independent variable (company size, tax and debt covenants) that affects accounting conservatism. The result of the analysis of the coefficient of determination (R2) or adjusted r square is 0.301 or 30.1%. In other words, the effect of independent variables (company size, taxes, and debt covenants) on the dependent variable (accounting conservatism) is 30.1% and the remaining 69.9% (100% - 30.1%) is influenced by other variables that are not investigated in this study. The result of the analysis of the coefficient of determination (R2) or adjusted r square is 0.301 or 30.1%. In other words, the effect of independent variables (company size, taxes, and debt covenants) on the dependent variable (accounting conservatism) is 30.1% and the remaining 69.9% (100% - 30.1%) is influenced by other variables that are not investigated in this study.In other words, the effect of independent variables (company size, taxes, and debt covenants) on the dependent variable (accounting conservatism) is 30.1% and the remaining 69.9% (100% - 30.1%) is influenced by other variables that are not investigated in this study.